2020
DOI: 10.3390/microorganisms8010113
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiotic and Paraprobiotic Potential Effect of Lactobacillus casei in a Systemic Toxoplasmosis Murine Model

Abstract: One of the main characteristics of probiotics is their ability to stimulate and modulate the immune response regardless of their viability. Lactobacillus casei (Lc) can stimulate local and systemic immunity, in addition to the activation of macrophages at sites distant from the intestine. Activated macrophages limit the replication of intracellular protozoa, such as Toxoplasma gondii, through the production of nitric oxide. The present study aimed to evaluate the protection generated by treatment with viable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…183261 and were given orally at a dose of one billion Lactobacilli per mouse, administered daily for 14 days, 7 days before infection, and 7 days p.i. (Salas-Lais et al 2020). They were prepared by dissolving each probiotic sachet that contains 10 billion Lactobacillus delbrueckii and Lactobacillus fermentum in 1 mL of distilled water to prepare the required concentration.…”
Section: Lactobacillus Probioticsmentioning
confidence: 99%
“…183261 and were given orally at a dose of one billion Lactobacilli per mouse, administered daily for 14 days, 7 days before infection, and 7 days p.i. (Salas-Lais et al 2020). They were prepared by dissolving each probiotic sachet that contains 10 billion Lactobacillus delbrueckii and Lactobacillus fermentum in 1 mL of distilled water to prepare the required concentration.…”
Section: Lactobacillus Probioticsmentioning
confidence: 99%
“…First, the CellROX ® Deep Red (5 µM) was added and the tubes were incubated for 30 min at 37 °C in 5% CO2 in the dark that, the DAF-FM DA probe (5 µM) was added to the tubes and they were incubat another 30 min. A separated tube of macrophages with the same assay conditions labeled with 4 µL of conjugated-APC monoclonal antibody anti-mouse F4/80 (Th Scientific, Eugene, OR, USA), incubating this for 30 min in darkness [28]. The analys performed on a BD FACSLyric™ Flow Cytometry System (Figure 1).…”
Section: Measurement Of the Production Of Reactive Oxygen (Ros) And N...mentioning
confidence: 99%
“…In HSV infection experiments using T cell defective mice such as nude mice and SCID mice, it has been reported that cellular immunity via T cells is essential for the elimination of HSV-infected cells (Minagawa and Yanagi, 2000), and an increase in the counts of CD8-positive T cells invading the ganglia inhibits the reactivation of latently infected HSV (Hoshino et al, 2007;Khanna et al, 2003;Liu et al, 2001), suggesting that the immune response in the host may play an important role in maintaining latent HSV infection. LcS has been reported to activate innate immunological effects and T cells in a live LcS-specific manner (Dong et al, 2010;Salas-Lais et al, 2020).…”
Section: Impact On Serum Viral Antibody Index Of Live Lcsmentioning
confidence: 99%